Emission Characteristics of Volatile Organic Compounds from Typical Coal Utilization Sources: A Case Study in Shanxi of Northern China - Yang Xu; Hualong Yu; Yulong Yan; Lin Peng; Rumei Li; Cheng Wang; Zhiyong Li (Aerosol and Air Quality Research)
Abstract China, where coal is the dominant energy resource, accounted for 50.5% of the world’s coal consumption—or 1906.7 million tons of oil equivalent—during 2018. As a major source of volatile organic compounds (VOCs), coal utilization also led to high national emissions of these pollutants. In this study, we investigated the profiles; benzene, toluene, ethylbenzene, and xylene (BTEX) ratios; ozone formation potential (OFP); and secondary organic aerosol (SOA) formation potential of VOCs generated by coal-utilizing steel plants, power plants, coking plants, and residential stoves in northern China. Among the detected VOCs, the results identified 1-butene as the most abundant species for both the power plants (36.7%) and the residential stoves (41.7%) as well as a significant contributor at the steel plants (7.3%), and alkenes, alkanes, and aromatics composed the largest groups for the power plants (42.0%) and residential stoves (60.2%); steel plants (59.2%); and coking plants (66.1%), respectively. Additionally, the VOC profiles for power plants employing the same coal source or combustion technology exhibited strong similarities, although the BTEX ratios varied more between plants using different coal sources than those using different combustion technologies. Finally, alkenes were primarily responsible for the ozone formation (73.1%, 59.0%, and 87.6% for the power plants, steel plants, and residential stoves, respectively), whereas aromatics were primarily responsible for the SOA formation (more than 94.0% for all four coal-utilizing sources).